PEMBERIAN TES PSIKOLOGI UNTUK MEMBANTU PEMILIHAN JURUSAN BAGI SISWA SMA DI KOTA PALEMBANG (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
The incompatibility of higher education taken with students' interests and the existence of professions that are not in accordance with their educational background are thought to be able to cause conflict within the individual who experiences it. Providing psychological test interventions to high school students who are preparing to enter college is expected to help students choose majors that suit their interests and abilities. Psychological tests were given to 58 high school students in the city of Palembang and surrounding areas without payment. Providing instructions and checking the results of filling out the psychological test is carried out by students of the Psychology study program at FK Sriwijaya University who have taken the Asesmen Dasar I course. It also give opportunity to train as testers. Before the psychological testing, a selection process for testers candidate was conducted by the supervising lecturer, resulting in the selection of 5 testers. The psychological test report regarding the interests and talents of the high school students was prepared by a psychologist who is also a lecturer in the same program to ensure compliance with the applicable psychological ethics code. The evaluation of the was carried out at the reaction and learning levels. At the reaction level, all participants expressed satisfaction and felt assisted by the implementation of the psychological tests. After all psychological test reports were provided to the participants, all reported gaining knowledge regarding the majors they would choose when continuing their education. This forms the evaluation results for the learning level.   ---   Ketidaksesuaian pendidikan tinggi yang diambil dengan minat siswa dan adanya profesi yang tidak sesuai dengan latar belakang pendidikan diduga akan dapat menimbulkan konflik dalam diri individu yang mengalaminya. Pemberian intervensi tes psikologi untuk mengetahui minat dan bakat kepada siswa SMA yang akan bersiap memasuki perguruan tinggi diharapkan dapat membantu siswa memilih jurusan yang sesuai dengan minat dan kemampuan. Pemberian psikotest diberikan kepada 58 siswa SMA di kota Palembang dan sekitarnya tanpa dikenakan bayaran. Pemberian instruksi dan pemeriksaan hasil pengisian psikotest dilakukan oleh mahasiswa program studi Psikologi FK universitas Sriwijaya yang telah mengambil mata kuliah Asesemen Dasar I sekaligus sebagai sarana praktek menjadi tester. Sebelum psikotest, diadakan seleksi terlebih dahulu untuk calon tester oleh dosen pengabdi dan terpilih 5 orang tester. Untuk laporan psikotest minat dan bakat siswa SMA dibuat oleh psikolog sekaligus dosen dari prodi yang sama agar tetap sesuai dengan kode etik psikologi yang berlaku. Evaluasi kegiatan pengabdian dilakukan pada level reaction dan learning. Dari penilaian yang disebarkan setelah proses pengambilan data psikotest untuk level reaction, seluruh peserta merasa puas dan terbantu dengan pelaksanaan psikotest. Setelah semua laporan psikotest diberikan kepada peserta, semua peserta melaporkan bahwa mereka menjadi memiliki pengetahuan terkait jurusan yang akan dipilih saat melanjutkan pendidikan nanti. Ini merupakan hasil evaluasi untuk level learning.
Keywords: Major; psychological testing; student